2005
DOI: 10.1152/ajpgi.00428.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycitric acid delays intestinal glucose absorption in rats

Abstract: In this study, we investigated in rats if hydroxycitric acid (HCA) reduces the postprandial glucose response by affecting gastric emptying or intestinal glucose absorption. We compared the effect of regulator HCA (310 mg/kg) and vehicle (control) on the glucose response after an intragastric or intraduodenal glucose load to investigate the role of altered gastric emptying. Steele's one-compartment model was used to investigate the effect of HCA on systemic glucose appearance after an intraduodenal glucose load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…A silicon catheter (1.40-mm OD, 0.80-mm ID) was inserted through the gastric wall at the level of the corpus, extending 0.5 cm into the gastric lumen. The catheter was drawn subcutaneous towards the head where it was fixed to the skull with dental cement (Wielinga et al, 2005). Animals were given 0.1 ml Finadine s.c. for analgesia and 0.25 ml penicillin s.c. to prevent infection.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…A silicon catheter (1.40-mm OD, 0.80-mm ID) was inserted through the gastric wall at the level of the corpus, extending 0.5 cm into the gastric lumen. The catheter was drawn subcutaneous towards the head where it was fixed to the skull with dental cement (Wielinga et al, 2005). Animals were given 0.1 ml Finadine s.c. for analgesia and 0.25 ml penicillin s.c. to prevent infection.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Thus, (-)-HCA supplementation is expected to alter metabolic pathways. Although some studies have shown (-)-HCA possesses anti-obesity activity [36, 37] and anti-diabetic activity [38, 39], little information is available on whether (-)-HCA affects fat accumulation in broiler chickens through regulation on the energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…A myriad of health effects have been attributed to Garcinia (including G. cambogia, G. atroviridis , and G. indica ), such as antiobesity effects [1517], antiulcerogenic [18–20], antioxidative [2124], antidiabetes [25], antimicrobial [22, 26–28], antifungal [29], anti-inflammatory [30, 31], and anticancer effects [22, 3234]. In particular, the antiobesity effects of Garcinia or more specifically of its HCA content have been elucidated with unprecedented clarity over the last few decades.…”
Section: Introductionmentioning
confidence: 99%